Morphological classification of childhood medulloblastomas with β-catenin immunohistochemistry and mycn fluorescent in situ hybridization - Okiro, Patricia Opon (University of Cape Town, 2015)
Medulloblastoma is the most frequently occurring childhood malignant brain tumour, affecting 1 of 5 children presenting with a brain tumour, between the ages of 0 and 9 years. The basic prognostic stratification that relies on clinical and histological findings alone has proven unsatisfactory as an outcome predictor. Distinct molecular genetic profiles have been described, with four molecular variants of medulloblastoma with specific demographic and prognostic features. These are the WNT subgroup, SHH subgroup, Group 3 and Group 4 tumours. The aim of this study was to describe the expression status of β-catenin, and MYCN, using IHC and FISH respectively, and to correlate these findings with clinico-pathological and demographic characteristics and clinical outcome. Materials and Methods This study was a nested retrospective analytical study, reviewing 54 cases of childhood medulloblastoma diagnosed between 1988 and 2014. Results Classic histology accounted for 40.7% of cases, LCA 37%, ND 16.7% and 5.6% MBEN). Based on β-catenin IHC, the WNT subgroup accounted for 16.7% of cases. This group had no mortalities or recurrences. Seven patients showed amplification of MYCN gene. The SHH group, defined by ND/MBEN histology and/or MYCN amplification, accounted for 27.7% of patients. Non-WNT/non-SHH tumours 30 patients (55.6%) showed a male predilection, and accounted for 37.5% recurrences and 50%. mortalities also falling in this group. Conclusions Nuclear β-catenin identifies WNT tumours. Nodular desmoplastic morphology is useful in identifying some, but not all cases of SHH group medulloblastomas. MYCN positive tumours also showed classical, and LCA morphology.. Patients of all the beta-catenin positive cases were free of recurrence and alive at last follow up. Patients with MYCN amplification and non-ND histology (LC/A or classic) had poorer outcomes than patients with ND histology. One patient showed both MYCN amplification and nuclear β-catenin translocation, and had good clinical outcome. This finding requires validation with other molecular techniques.